Estimating the Concentrations of Some Adipokines and Biochemical Parameters in Women with Polycystic Ovary Syndrome - Ahmed, Ahmed Shakir; Ibrahim, Nawar Tariq; Faisal, Ragheed Raad (American Journal of Biology and Natural Sciences, 2025)
Endometriosis and polycystic ovarian syndrome (PCOS) are common disorders of the female reproductive system that have a high morbidity rate because they can considerably impair fertility and quality of life. Adipokines, which play a crucial role in energy metabolism, are pleiotropic signaling molecules released by either brown or white adipose cells. Therefore, the goal of the current study was to evaluate the levels of certain adipokines and biochemical markers in women who have polycystic ovarian syndrome. In the labs of the Teaching Azadi Hospital, this study was conducted from June to February 2024. The samples for the study were submitted by 90 women, ages 15 to 45. These samples were divided into the following two groups: Control group: Thirty healthy women's blood samples were collected during the follicular phase of their menstrual cycles. Patient group: Blood samples from 50 PCOS women were obtained during the follicular phase. The findings showed that the high percentage of PCOS was found in 26-35year group that reach to 46.7%, the average age of women with PCOS was 28.83±4.11 years. Also, it is noted that the group of women who weighed more than 30 kg/m2 had the highest percentage reached 58.9%. Serum levels of adiponectin in individuals with PCOS were significantly (P <0.05) lower (2.74±0.19) than in healthy women (6.21±0.33). PCOS patients' leptin levels were significantly (P <0.05) higher (26.57 ± 2.15) than those of healthy women (9.05 ± 0.26). Chemerin levels in females with PCOS were significantly (P <0.05) higher (21.85 ± 1.62) than in healthy women (4.84 ± 0.52). The study found that polycystic ovarian syndrome (PCOS) in women is strongly correlated with adipokines, and that PCOS is also correlated with body mass index.